1995
DOI: 10.1097/00000658-199509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Laparoscopic Appendectomy A Prospective Randomized Comparison

Abstract: ObjectiveThe authors compare open and laparoscopic appendectomy in a randomized fashion with regard to length of operation, complications, hospital stay, and recovery time. MethodsAdult patients (older than 14 years of age) with the diagnosis of acute appendicitis were randomized to either open or laparoscopic appendectomy over a 9-month period. All

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
3
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(159 citation statements)
references
References 15 publications
14
135
3
7
Order By: Relevance
“…Most of the study also reported that postoperative complications are more related to severity of underlying pathology than the type of procedure. 9,16 The results demonstrate a significantly earlier return to full activity for laparoscopic than open appendectomy. This is parallel with the results shown by other research worker in most of the studies.…”
Section: Figure 1: Hospital Staymentioning
confidence: 82%
“…Most of the study also reported that postoperative complications are more related to severity of underlying pathology than the type of procedure. 9,16 The results demonstrate a significantly earlier return to full activity for laparoscopic than open appendectomy. This is parallel with the results shown by other research worker in most of the studies.…”
Section: Figure 1: Hospital Staymentioning
confidence: 82%
“…Pneumoperitoneum during a laparoscopic appendicectomy also increases the risk of general anesthesia-related complications in elderly patients (8). Furthermore, 10% of laparoscopic surgeries may need conversion to open appendicectomies, mainly with highgrade inflammation (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to conventional surgery, laparoscopy reduces postoperative pain and the hospital stay, and allows the patient to resume normal activities more rapidly [9,10]. However, it remains controversial because of the lengthy surgery, the relatively high morbidity, and problems in respecting oncological principles in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…en bloc removal of the kidney, adrenal gland, Gerota's fascia and pararenal fat [3][4][5]. Laparoscopic RN (LRN) can be preformed either by the transperitoneal [6] or retroperitoneal approach [7][8][9]. In our institution we initially used LRN by the retroperitoneal approach; in the present study we compared the results of retroperitoneal LRN with open RN in patients with T1 lesions.…”
Section: Introductionmentioning
confidence: 99%